Clinical features and genetic analysis of acrodermatitis enteropathica in an ethnic minority infant from Western China: a case report and literature review - Axirejiang, Tuerhongjiang; Simayi, Gulinigeer; Abuduwake, Abudushalamu; Liu, Yunxia; Zheng, Gang; Ibrahim, Irshat (Frontiers in Medicine, 2025)
BackgroundAcrodermatitis enteropathy (AE) is a rare autosomal recessive disorder caused by mutations in the SLC39A4 gene. It is characterized by acral and perioral dermatitis, alopecia, and diarrhea. We reported the clinical features, genetic findings, and treatment response of a minority ethnic infant with AE from Xinjiang, China, and reviewed advances in AE management.Case descriptionA 10-month-old minority female infant presented with characteristic perioral, acral, and perianal erythematous erosions; alopecia; and diarrhea. Her serum zinc level significantly decreased (0.19 mg/L). Whole-exome sequencing revealed a homozygous c.197G > T(p. C66F) mutation in the SLC39A4 gene. Her skin lesions improved, her hair regrew, and her serum zinc level increased to 0.62 mg/L following zinc supplementation (3 mg/kg/d) and comprehensive treatment.ConclusionThis is the first case of AE in a Xinjiang minority infant and implicates SLC39A4 mutations in its pathogenesis and zinc therapy efficacy. This case provides insights into the genetic and clinical features of AE across Chinese ethnic groups, emphasizing early genetic testing and individualized zinc therapy. Primary physicians should consider AEs in infants with characteristic dermatitis, alopecia, and diarrhea. The zinc levels should be measured promptly, and genetic analysis should be conducted to prevent misdiagnosis and treatment delays.